Advances in Human Factors in Cybersecurity Proceedings of the AHFE 2016 International Conference on Human Factors in Cybersecurity, July 27-31, 2016, Walt Disney World®, Florida, USA - Nicholson, Denise (Advances in Intelligent Systems and Computing,, 2016)
This book reports on the latest research and developments in the field of cybersecurity, giving a special emphasis on personal security and new methods for reducing human error and increasing cyber awareness, and innovative solutions for increasing the security of advanced Information Technology (IT) infrastructures. It covers a wealth of topics, including methods for human training, novel Cyber-Physical and Process-Control Systems, social, economic and behavioral aspects of the cyberspace, issues concerning the cyber security index, security metrics for enterprises, risk evaluation, and many others. Based on the AHFE 2016 International Conference on Human Factors in Cybersecurity, held on July 27-31, 2016, in Walt Disney World®, Florida, USA, this book not only presents innovative cybersecurity technologies, but also discusses emerging threats, current gaps in the available systems and future challenges that may be coped with through the help of human factors research.